PENGARUH KUALITAS LAYANAN TERHADAP LOYALITAS PELANGGAN PADA ALFAMART KAYUAGUNG - Fernandes, Ari (Universitas Muhammadiyah Palembang, 2021)
Purpose This research was conducted at the Kayuagung Alfamart branch in Jalan Lt. Muchtar Saleh Kayuagung OKI. The objectives to be achieved in this research are: to find out how the influence of Service Quality on Customer Loyalty at Alfamart Kayuagung. Design / methodology is the type of field research research, namely research that comes directly to the field where the research is conducted (Sugiono, 2009: 494). ). Operational Definition of Variables 1. independent variable (x), namely the quality of services provided by Alfamart. 2 dependent variables (y), namely customer loyalty or customer loyalty using Alfamart servicesIn this study using data collection techniques in the form of a questionnaire or questionnaire, with the hypothesis: = There is a significant positive relationship between service quality and consumer loyalty at Alfamart Kayuagung. = There is a significant influence between service quality and customer loyalty of Alfamart Kayuagung.To simplify the analysis, the SPSS data processing application is usedFindings The findings show that: 1. The influence of service quality on customer loyalty at Alfamart kayuagung is considered quite large, namely 0.468 or 46.8%.2. The factors that influence service quality on customer loyalty based on the results of tabulation of the respondents' questionnaire answers include service quality indicators, namely reliability, responsiveness, confidence, empathy (empathy), and tangibility. 0% of respondents strongly agree, 48.3% of respondents strongly agree, 17.1% of respondents answered neutral, 31.7% of respondents disagreed and 2.9% of respondents strongly disagreed with service quality affecting customer loyalty of Alfamart Kayuagung